Nonsteroidal anti-inflammatory drugs (NSAID) do not increase blood loss or the incidence of postoperative epidural hematomas when using minimally invasive fusion techniques in the degenerative lumbar spine - Senker, Wolfgang; Aspalter, Stefan; Trutschnig, Wolfgang; Franke, Jörg; Gruber, Andreas; Stefanits, Harald (Frontiers in Surgery, 2022)
Objective: Nonsteroidal anti-inflammatory drugs (NSAID) are essential in surgeons’ armamentarium for pain relief and antiphlogistic effects. However, spine surgeons are concerned about the drugs’ impact on coagulation, fearing hemodynamic instability due to blood loss and neurological complications due to postoperative hematoma. Furthermore, there are no clear guidelines for the use of these drugs. Materials and methods: In this retrospective subgroup analysis of a prospective observational study, we investigated 181 patients who underwent minimally invasive spinal fusions in degenerative lumbar spine pathologies. 83 patients were given NSAID perioperatively, 54 of which were female and 29 male. Of these patients who took NSAID, 39 were on NSAID until at least one day before surgery or perioperatively, whilst the others discontinued their NSAID medication at least three days before surgery. Differences in perioperative blood loss, as well as complication rates between patients with and without NSAID treatment, were investigated. Results: A significantly higher amount of blood loss during surgery and the monitoring period was encountered in patients whose spine was fused in more than one level, regardless of whether NSAID medication was taken or not and up until what point. Furthermore, it was found that taking NSAID medication had no effect on the incidence of postoperative epidural hematomas. Conclusion: Perioperatively taking NSAID medication does not increase blood loss or the incidence of postoperative hematoma in patients undergoing minimally invasive lumbar spinal fusion surgery.